Manufacture of large-scale space exploration components using wire + arc additive manufacturing - Diao, Chenglei; Eimer, Eloise; Mancini, Simone; Krishnaswamy, Surya; Schwarz, Florian; Pagone, Emanuele; Ding, Jialuo; Williams, Stewart; Pinter, Zsolt; Martina, Filomeno (International Council of the Aeronautical Sciences (ICAS), 2022)
Cranfield University, Thales Alenia Space and WAAM3D together, combining their expertise knowledge and technologies on Wire + arc additive manufacture (WAAM), created a route for manufacturing large-scale space exploration Components using WAAM which could be used in future large scale-space exploration component manufacturing. In this project, several different sections of the development of WAAM technology are applied to manufacture a large-scale space exploration component including FEA simulation, inter-layer machining and cold work, intelligent toolpath planning and sustainability calculations. WAAM proved to be a very promising technique in future large-scale component manufacturing.
Keywords: Wire + Arc Additive Manufacturing; inter-layer machining and cold work; intelligent tool path planning; FEA distortion prediction; sustainability and environment protection